Curing of degraded MAPbI3 perovskite films. Issue 65 (23rd June 2016) - Guo, Xin; McCleese, Christopher; Lin, Wei-Chun; Burda, Clemens
Abstract : Perovskite films were prepared using a one-step solution deposition. Such films degrade over time because of the ambient humidity. Curing of degraded films through X-ray, UV and electron beam irradiation is demonstrated. Abstract : Perovskite films were prepared using one-step solution deposition. The prepared films were degraded for 14 days under ambient atmosphere with controlled humidity of 60 ± 5%. The degraded films showed separated regions of PbI2 -rich and methylammonium iodide (MAI)-rich phases. Through X-ray, UV and electron beam irradiation, a fast recovery of perovskite was initiated in the MAI regions and the photoproduct further spread into the PbI2 regions over a time frame of minutes. Ultraviolet and electron beam were also explored as irradiation sources and the same photoinduced perovskite formation was observed in each case. XRD results proved that the photoproduct is indeed tetragonal perovskite MAPbI3 . A slower conversion process can be achieved by storing the degraded samples at 25% ± 5% humidity. It is also observed that samples degraded at high humidity can be recovered by thermal annealing at a temperature as low as 35 °C. In this work, recovery of the aged perovskite films from decomposed phases (intermediate phase and PbI2 ) is shown to be feasible, which paves a new way for sustainable perovskite-based solar cells.